Eros e o livro-viagem: outra leitura de Galáxias de Haroldo de Campos - Bomfim, Monalisa Medrado (Universidade Federal de São Carlos, 2024)
The objective of this research was to discuss Galáxias, by Haroldo de Campos, from the perspective of the poem's erotic language. The galactic fragments present different levels of eroticism and, therefore, were analyzed based on the pleasure of the text, in which the erotic manifests itself at the limit of the fruition of languages, which in Galáxias also converges with the figures of women. Since the book presupposes a free reading of the pages, the analysis regrouped the fragments into constellations that privilege the protagonism of women, exploring the palimpsest constitution of the characters of the sea-woman, the prostitute-priestesses, the Dantesque Beatrice, Marilyn Monroe and the city-women. Each fragment of the poem reveals parts of these bodies, which synchronously combine into a single woman: the muse, the logopoeic center of the poem. In order to do so, eroticism was discussed based on the theories developed by Georges Bataille and Eliane Moraes, the latter of which advances the delineation of the erotic in Brazilian literature. The formal resources of erotic language were examined based on the concepts of Roland Barthes and Severo Sarduy. It should also be noted that there are several women in the poem, represented in different geographical and historical contexts; the analysis sought to highlight them, outlining a synchronic-diachronic study. The research, therefore, highlighted the erotic aspects of Galáxias, especially those linked to the depiction of women, understood as central elements of the poem's signifying system.
Eros and the travel-book: another reading of Galaxies by Haroldo de Campos
Keywords: Erotismo; Galáxias; Haroldo de Campos; Mulheres; Poesia brasileira; LINGUISTICA, LETRAS E ARTES::LETRAS::LITERATURA BRASILEIRA; 5. Igualdade de Gênero